COMPARATIVE CHARACTERISTICS OF LEUKOCYTOSIS LEVEL, C_REACTIVE PROTEIN, PROCALCITONIN IN DIFFERENTIAL DIAGNOSTICS OF ACUTE TONSILLITES AMONG CHILDREN - E.V. Starorovoitova; V.V. Botvin'eva; A.M. Fedorov; V.K. Tatochenko; M.D. Bakradze; A.S. Darmanyan (Union of pediatricians of Russia, 2007)
The authors appraised the diagnostic value (sensitivity, specificity, positive and negative prognostic values) of leukocytes, concentration of c reactive protein, procalcitonin in the blood of children with fever and symptoms of acute tonsillitis. They provided comparative characteristics of these indices during tonsillitises of various etiology. It was stressed that the concentration of leukocytes of 10-15_109/l was not a reliable marker of the bacterial infection, while c reactive protein as a marker of the bacterial inflammation had some average sensitivity and specificity values and procalcitonin had the highest specificity.Key words: acute tonsillitis, fever, children, leukocytosis, c_reactive protein, procalcitonin.